Effectiveness of E-Booklets on Pregnant Women's Knowledge of Balanced Nutrition - Widayati, Widayati; Windayanti, Hapsari; Kristiningrum, Wahyu; Afriyani, Luvi Dian (Jurnal Kesehatan, 2025)
Low nutritional intake and knowledge among mothers during pregnancy are important factors that influence the occurrence of KEK and the risk of stunting. Efforts to increase knowledge are usually carried out through posyandu counseling or information media. This study aims to determine the effectiveness of e-booklets on pregnant women's knowledge of balanced nutrition. The research method included a pre-experimental pre-test and post-test (single-group pretest-posttest design) with 21 pregnant women selected via incidental sampling from a population of 31. The measurement tool used a questionnaire consisting of 35 questions, with a calculated r value of 0.369-0.784 and a Cronbach's Alpha of 0.91. The data were analyzed using the Wilcoxon test because they were not normally distributed. The test results showed a p-value of 0.001, indicating that the e-booklet was effective in improving pregnant women's knowledge of balanced nutrition. Future researchers should conduct further randomized controlled trials (RCTs) to test the effectiveness of e-booklets, using a control group and a larger sample size, or to evaluate their impact on nutritional behavior/practices.